STATE OF THE ART IN PROTEOMICS FOR CANCER DETECTION - Syafrizayanti Syafrizayanti (Faculty of Medicine, Universitas Andalas, 2014)
The earliest stages of cancer detection determine the successful of cancer treatment andtherapy. The existing cancer test or detection methods have been routinely used, but they arelack of sensitivity and specificity that are needed to avoid false positive or negative results. Thegenomic basedtechniques have been applied, although molecular understandings of cancerfar from complete, but few genomic platforms are becoming routine. Application of proteomicsbasedtechniques provide intriguing outcome, which is cancer detection at their earliest stages.Proteomics have exposed a new perspective into the phases of tumorigenesis and depictedmore detailed molecular network scheme, which made important contributions in the discoveryof biomarker of early diagnosis, prognosis and prediction outcome of cancer therapies.The noticeable proteomic platforms to achieve these goals are protein microarray, tissuemicroarray, mass spectrometry-based proteomic, and two-dimensionalgel electrophoresis (2-DE). The application of these techniques will be overviewed, providing a general review ofcurrent proteomic methods in cancer detection and subsequently improvement in prognosisand prediction of cancer therapies.Keywords: proteomics, protein microarrays, mass spectrometry, cancer biomarkerAbstrakDeteksi dini kanker sangat menentukan keberhasilan penanganan dan terapi kanker. Hinggasaat ini, telah banyak jenis metoda deteksi dan uji kanker yang sudah rutin digunakan, akantetapi metoda-metoda tersebut memiliki tingkat sensitifitas dan spesifikasi yang rendah,sehingga sering menyebabkan terjadi kesalahan hasil uji baik secara positif ataupun negatif.Bidang genomik telah banyak digunakan untuk lebih memahami kanker pada level molekuler,meskipun hasil yang diperoleh belum mendalam, akan tetapi beberapa metoda berbasiskangenomik telah mulai rutin digunakan. Bidang pioteomik mulai banyak diaplikasikan untukkeperluan deteksi kankersedini mungkin. Proteomik memberikan perspektif dalam mempelajarifase-fase pembentukan tumor dan juga bisa memberikan gambaran rangkaian molekuler yangterlibat. Hasil ini akan menjadi suatu kosntribusi yang sangat besar untuk mencari biomarkeruntuk diagnosa awal, prognosa dan dan memprediksikan luaran terapiyang muncul. Beberapametoda proteomik telah banyak digunakan untuk tujuan tersebut, diantaranya adalah proteinmicroarrays, fissue microarrays, /nass spectrometry-based proteomic, dan two-dimensionalgel electrophoresis (2-DE). Beberapa aplikasi teknik proteomik tersebut akan dibahas padatulisan ini, sehingga bisa memberikan pandangan umum tentang metoda-metoda proteomikterkini yang sudah mulai digunakan untuk deteksi kanker dan selanjutnya memperbaikiprognosa yang diberikan dan bias memantau luaran yang dihasilkan dariterapi.